Mutation of brain aromatase disrupts spawning behavior and reproductive health in female zebrafish - Shaw, Katherine; Therrien, Mylène; Lu, Chunyu; Liu, Xiaochun; Trudeau, Vance L. (Frontiers in Endocrinology, 2023)
Aromatase (Cyp19a1) is the steroidogenic enzyme that converts androgens into bioactive estrogens, and hence is in a pivotal position to mediate reproduction and sexual behavior. In teleosts, there are two aromatase paralogs: cyp19a1a that is highly expressed in granulosa and Leydig cells in the gonads with critical function in sexual differentiation of the ovary, and cyp19a1b that is highly expressed in radial glial cells in the brain with unknown roles in reproduction. Cyp19a1 -/- mutant zebrafish lines were used to investigate the importance of the cyp19a1 paralogs for spawning behavior and offspring survival and early development. Mutation of cyp19a1b was found to increase the latency to the first oviposition in females. Mutation of cyp19a1b in females also increased the number of eggs spawned; however, significantly more progeny died during early development resulting in no net increase in female fecundity. This finding suggests a higher metabolic cost of reproduction in cyp19a1b -/- mutant females. In males, the combined mutation of both cyp19a1 paralogs resulted in significantly lower progeny survival rates, indicating a critical function of cyp19a1 during early larval development. These data establish the specific importance of cyp19a1b for female spawning behavior and the importance of the cyp19a1 paralogs for early larval survival.